The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s12032-011-0001-2
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant concurrent chemoradiotherapy with capecitabine and oxaliplatin in patients with locally advanced esophegeal cancer

Abstract: Evaluation of the feasibility and efficacy of neoadjuvant concurrent chemoradiotherapy (CRT) with capecitabine and oxaliplatin in patients with locally advanced esophageal cancer. Forty-two patients were eligible for the study. The chemotherapy during CRT consisted of two cycles of intravenous oxaliplatin of 120 mg/m(2) on day 1 and oral capecitabine 825 mg/m(2) twice daily on days 1-14 at 3-week intervals. The radiotherapy (1.8 Gy/fraction/day to a total dose of 45 Gy) was delivered to the primary tumor site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…In our series, toxicity was acceptable, with most adverse events being grade 1 or 2, and no treatmentrelated deaths being recorded. Dose reduction was required in 8 patients, and rates of grades 3 and 4 hematologic and nonhematologic toxicities were similar to those reported in other phase ii trials of preoperative crt (including oxaliplatin and 5fu-based chemotherapy) in esophageal or gej cancer [29][30][31][32] and also by our group in earlier work involving resected high-risk gastric cancer patients 13 . Those results are particularly interesting because our study used a higher radiotherapy dose than that reported in the German study (45 Gy vs. 30 Gy).…”
Section: Discussionsupporting
confidence: 79%
“…In our series, toxicity was acceptable, with most adverse events being grade 1 or 2, and no treatmentrelated deaths being recorded. Dose reduction was required in 8 patients, and rates of grades 3 and 4 hematologic and nonhematologic toxicities were similar to those reported in other phase ii trials of preoperative crt (including oxaliplatin and 5fu-based chemotherapy) in esophageal or gej cancer [29][30][31][32] and also by our group in earlier work involving resected high-risk gastric cancer patients 13 . Those results are particularly interesting because our study used a higher radiotherapy dose than that reported in the German study (45 Gy vs. 30 Gy).…”
Section: Discussionsupporting
confidence: 79%
“…Single arm phase I–II studies have demonstrated feasibility of oxaliplatin-based nCRT [9], [10], [11], [12], [13], [14], [15]. One randomised phase II study comparing oxaliplatin-5FU-based CRT with cisplatin 5FU-based CRT in patients with inoperable but localised oesophageal cancer has demonstrated no significant difference in survival or toxicity but the ease of administration of oxaliplatin over cisplatin makes it a more attractive option [16].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Although various chemotherapy regimens are available, esophageal cancer carries a very poor prognosis, with a mean survival time of less than 8.1 months. 5 Currently, neoadjuvant treatment (such as capecitabine and cisplatin with concurrent radiotherapy (RT) followed by esophagectomy) is considered the effective treatment for esophageal cancer, 6,7 leading to complete pathologic response at the time of surgical resection and improved local tumor control and eradication of micrometastases. 8 Clearly, the development of novel and potent therapeutics in/not in combination with RT to improve both local and distant tumor control in esophageal cancer is an urgent task.…”
Section: Introductionmentioning
confidence: 99%